PENGARUH SUKU BUNGA, INFLASI, DAN NILAI TUKAR TERHADAP RETURN SAHAM PADA PERUSAHAAN PERBANKAN YANG TERDAPAT DI BEI TAHUN 2019-2022 - Bastiana, Angela Aprilia; Gunadi, I Gusti Ngurah Bagus; Suarjana, I Wayan (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2024)
The Share returns in five manufacturing companies experienced a decline. This is indicated by the stock returns obtained by the two companies which are not good, with a decrease in the percentage of stock returns which will influence investment decisions in this sector. This is due to a decline in banking company stock returns in 2021, one of which is caused by the decline in share prices. This research aims to determine the influence of interest rates, inflation and exchange rates on stock returns of banking companies listed on the IDX in 2019-2022. The location of this research was carried out at banking companies listed on the Indonesia Stock Exchange from 2019 to 2022. The data type used quantitative data and qualitative data. The data source uses secondary data sources. The population of this research is all banking companies listed on the Indonesia Stock Exchange from 2019 to 2022. The data collection method uses observation and documentation data. The data analysis technique uses multiple linear regression tests. The research results show that interest rates, inflation and exchange rates have no effect on stock returns.